The Effect of Return on Assets, Return on Equity and Debt to Equity Ratio on Stock Returns in Clothing and Luxury Goods Sub Sector Companies Listed on the Indonesia Stock Exchange - Wulansari Rijata; Maria Lusiana Yulianti; Deden Komar Priatna; Winna Roswinna (DINASTI RESEARCH, 2022)
This study aims to determine the effect of return on assets, return on equity, and debt to equity ratio on stock returns in clothing and luxury goods sub-sector companies on the Indonesian stock exchange. The method used in this research is a quantitative method. The data used in this study is secondary data obtained from the financial statements of 6 companies through the Indonesian Stock Exchange website for 2017-2021. The sampling technique used purposive sampling method. The total research data obtained is 30 data.The results showed that the return on assets has a positive effect on stock returns, while the return on equity and debt to equity ratio have no effect on stock returns. Suggestions for companies to pay attention to the return on assets because it can affect stock returns. For future researchers, it is hoped that they can add or replace other independent variables related to changes in stock returns.